2019
DOI: 10.11591/edulearn.v13i1.8357
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual understanding of high school students on plantae

Abstract: Kingdom Plantae is a topic taught in Grade Tenth in Indonesia high school. The previous researchers have found misconceptions and difficulties in understanding the classification and the nomenclature system of Kingdom Plantae. Understanding basic concepts of Kingdom Plantae is important to study the more complex system of Plantae. This research was aimed to analyze the conceptual understanding of high school students on Plantae. The participants were 372 eleven graders who had studied Kingdom Plantae and selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(14 reference statements)
0
2
0
3
Order By: Relevance
“…Miskonsepsi bisa terdapat pada semua konsep biologi. Choirina, Ramli & Rinanto (2019) juga mengungkapkan bahwa terdapat miskonsepsi pada konsep biologi yaitu tentang kingdom plantae meliputi monokotil dan dikotil, morfologi Anacardium occidentale, Musa sp. dan Solanum tuberosum, klasifikasi Anacardium occidentale.…”
Section: Pembahasanunclassified
“…Miskonsepsi bisa terdapat pada semua konsep biologi. Choirina, Ramli & Rinanto (2019) juga mengungkapkan bahwa terdapat miskonsepsi pada konsep biologi yaitu tentang kingdom plantae meliputi monokotil dan dikotil, morfologi Anacardium occidentale, Musa sp. dan Solanum tuberosum, klasifikasi Anacardium occidentale.…”
Section: Pembahasanunclassified
“…The way that students can learn plants easily is by having an understanding of them. The students who have mastered the concept will be able to remember it, which has been learned over a long period of time to make the learning meaningful (Choirina et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies examining how well students understood food production and growth in plants indicated that students had a considerable degree of misconceptions in various grade levels, and these misconceptions were resistant to change by traditional teaching methods (ALkhawaldeh, 2019;Balci et al, 2006;Choirina et al, 2019;Chuenmanee & Thathong, 2017;Galvin et al, 2015;Griffard & Wandersee, 2001;Lin, 2004;Marmaroti & Galanopoulou, 2006;Parker et al, 2012;Skribe Dimec & Strgar, 2017;Vitharana, 2015;Woldeamanuel et al, 2020). Furthermore, most of the teachers have difficulty diagnosing their students' learning problems or misconceptions in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini dikarenakan konsep Plantae merupakan konsep dasar dalam biologi sebelum peserta didik belajar mengenai konsep biologi di tingkat berikutnya. Jika peserta didik tidak memahami konsep Plantae, maka peserta didik akan kesulitan untuk memahami konsep selanjutnya tentang Plantae (Choirina, et. al., 2019).…”
unclassified
“…Selain itu, miskonsepsi siswa berbeda antara strobil jantan dan betina pada tumbuhan pinus dan strobil jantan dan betina pada melinja (Setiawan et al, 2014). Kurangnya penguasaan konsep Plantae oleh siswa dapat disebabkan oleh beberapa faktor, seperti penggunaan model pembelajaran Plantae dan proses pembelajaran Plantae yang tidak dilaksanakan secara kontekstual (Choirina, et al, 2019). Oleh karena itu, diperlukan inovasi dalam pembelajaran untuk meningkatkan pengelolaan konsep plantae (Wildani, 2016).…”
unclassified